Implementation of Local Wisdom-based Teaching at the Right Level (TaRL) Approach to Improve Students’ Learning Outcomes - Fitriyah, Khoirotul; Annizar, Anas Ma'ruf (Indonesian Journal of Mathematics and Natural Science Education, 2024)
This study aims to implement the local wisdom-based Teaching at the Right Level (TaRL) approach to improve students’ learning outcomes. This study used a class action research approach. Findings indicate that the average percentage of student learning outcomes in cycle 1 reached in the excellent category with the percentage of 22, the good category with the percentage of 7, the moderate category was 15%, and the bad category was 22%. In cycle II, the learning outcomes of students reached an increase indicating scores in the very good category of 37%, in the good category of 7%, in the moderate category of 22%, and in the bad category of 7%. The results of the implementation show that there was a significant increase in the learning outcomes of fourth grade students of SDN Tegal Gede 3 Jember. In cycle 1, there was an increase of 48% in learner completeness, which then increased to 70% in cycle II. To conclude, the implementation of local wisdom-based Teaching at the Right Level (TaRL) approach is able to improve students’ learning outcomes.